Orally Administered Antibiotics Vancomycin and Ampicillin Cause Cognitive Impairment With Gut Dysbiosis in Mice With Transient Global Forebrain Ischemia - Lee, Kyung-Eon; Kim, Jeon-Kyung; Kim, Dong-Hyun (Frontiers in Microbiology, 2020)
Gut microbiota is closely associated with the occurrence of neuropsychiatric disorders. Antibiotics are frequently used to prevent pathogen infection in patients with brain ischemia. To understand the impact of prophylactic antibiotic treatment for patients with brain ischemia, we examined the effects of orally administered vancomycin and ampicillin on cognitive function and gut microbiota composition in mice with transient global forebrain ischemia (tIsc). tIsc operation and orally gavaged vancomycin mildly and moderately caused cognitive impairment, respectively. However, the exposure of mice with tIsc to vancomycin or ampicillin severely impaired cognitive function in the Y-maze, novel object recognition, and Banes maze tasks. Furthermore, their treatments induced NF-κB activation as well as active microglia (NF-κB+/Iba1+ and LPS+/Iba1+ cells) and apoptotic (caspase 3+/NeuN+) cell population in the hippocampus, whereas the brain-derived neurotrophic factor (BDNF)+/NeuN+ cell populations decreased. These treatments also caused colitis and gut dysbiosis. They increased the population of Proteobacteria including Enterobacter xiangfangenesis. Orally delivered fecal transplantation of vancomycin-treated mice with or without tIsc and oral gavage of Enterobacter xiangfangenesis also significantly deteriorated the cognitive impairment and colitis in transplanted mice with tIsc. These findings suggest that oral administration of antibiotics can deteriorate cognitive impairment with gut dysbiosis in patients with brain ischemia.